Low red to far-red light ratio promotes salt tolerance by improving leaf photosynthetic capacity in cucumber - Miao, Yanxiu; Gao, Xingxing; Li, Bin; Wang, Wenjiao; Bai, Longqiang (Frontiers in Plant Science, 2023)
Soil salinity severely inhibits leaf photosynthesis and limits agricultural production. Red to far-red light ratio (R/FR) affects leaf photosynthesis under salt stress, however, its regulation mechanism is still largely unknown. This study investigated the effects of different R/FR on plant growth, gas exchange parameters, photosynthetic electron transport, Calvin cycle and key gene expression under salt stress. Cucumber seedlings were exposed to four treatments including 0 mM NaCl and R/FR=7 (L7, control), 0 mM NaCl and R/FR=0.7 (L0.7), 80 mM NaCl and R/FR=7 (H7) and 80 mM NaCl and R/FR=0.7 (H0.7) for 9 days in an artificial climate chamber. The results showed that compared to L7 treatment, H7 treatment significantly reduced relative growth rate (RGR), CO2 assimilation rate (Pn), maximum photochemical efficiency PSII (Fv/Fm), most JIP-test parameters and total Rubisco activity, indicating that salt stress severely inhibited photosynthetic electron transport from PSII to PSI and blocked Calvin cycle in cucumber leaves. However, these suppressions were effectively alleviated by low R/FR addition (H0.7 treatment). Compared to H7 treatment, H0.7 treatment significantly increased RGR and Pn by 209.09% and 7.59%, respectively, enhanced Fv/Fm, maximum quantum yield for primary photochemistry (φPo), quantum yield for electron transport (φEo) and total Rubisco activity by 192.31%, 17.6%, 36.84% and 37.08%, respectively, and largely up-regulated expressions of most key genes involved in electron transport and Calvin cycle. In conclusion, low R/FR effectively alleviated the negative effects of salt stress on leaf photosynthesis by accelerating photosynthetic electron transport from PSII to PQ pool and promoting Calvin cycle in cucumber plants. It provides a novel environmentally friendly light-quality regulation technology for high efficiency salt-resistant vegetable production.